Factors Influencing information Sources - A study of Causal Relationship - Malhotra, S P; Saha, D K; Krishna, G V.S.R (Annals of Arid Zone, 2016)
Considering the importance of communication in adoption of agricultural innovations a study was undertaken to examine the causal relationship of information sources with different factors influencing adoption. The technique of path co-efficient analysis has been used in studying the causal relationships among the variables under consideration. Path-coefficients indicated that systemic linkage had highest direct effect (0.4224) with information sources followed by social participation (0.2829). The multiple regression analysis also revealed that most of the variation (66%) in the information sources was accounted by the systemic linkage and social participation which showed highest direct effects in the path analysis.